DETERMINATION OF THE POSSIBILITY OF REAL FLUX IN WATER NETWORKS (Municipal economy of cities. Series: «Economy science», 2013)
The article deals with the optimization of flow control in water networks. For this purpose it is proposed to use the developed program, which allows to determine the costs of water on parts of the network based on the values of pressure measured in individual nodes.